Pneumomediastinum in COVID-19 patients: a case series of a rare complication - Volpi, Sara (Eur J Cardiothorac Surg, 2020)
Pneumomediastinum is a rare clinical finding, but one which can be the source of significant concern for clinicians. By presenting 3 such cases, we highlight that pneumomediastinum can complicate the course of a severe coronavirus disease 2019 infection but emphasize that conservative management is the first-line method of treatment, with gradual resorption of the air from the tissues. It is important to be alert to the development of pneumothorax, which will require drainage.